Increasing Use of Cardiac and Pulmonary Rehabilitation in Traditional and Community Settings: OPPORTUNITIES TO REDUCE HEALTH CARE DISPARITIES. Issue 6 (November 2020) - Fleg, Jerome L.; Keteyian, Steven J.; Peterson, Pamela N.; Benzo, Roberto; Finkelstein, Joseph; Forman, Daniel E.; Gaalema, Diann E.; Cooper, Lawton S.; Punturieri, Antonello; Joseph, Lyndon; Shero, Susan; Zieman, Susan
Abstract : Although both cardiac rehabilitation (CR) and pulmonary rehabilitation (PR) are recommended by clinical practice guidelines and covered by most insurers, they remain severely underutilized. To address this problem, the National Heart, Lung, and Blood Institute (NHLBI), in collaboration with the National Institute on Aging (NIA), developed Funding Opportunity Announcements (FOAs) in late 2017 to support phase II clinical trials to increase the uptake of CR and PR in traditional and community settings. The objectives of these FOAs were to (1) test strategies that will lead to increased use of CR and PR in the US population who are eligible based on clinical guidelines; (2) test strategies to reduce disparities in the use of CR and PR based on age, gender, race/ethnicity, and socioeconomic status; and (3) test whether increased use of CR and PR, whether by traditional center-based or new models, is accompanied by improvements in relevant clinical and patient-centered outcomes, including exercise capacity, cardiovascular and pulmonary risk factors, and quality of life. Five NHLBI grants and a single NIA grant were funded in the summer of 2018 for this CR/PR collaborative initiative. A brief description of the research to be developed in each grant is provided. Abstract : Five National Heart, Lung, and Blood Institute grants and a single National Institute on Aging grant were funded in the summer of 2018 for this cardiac rehabilitation/pulmonary rehabilitation collaborative initiative. A brief description of the research to be developed in each grant is provided.